2003
DOI: 10.1021/es034155t
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Lead from Computer Printed Wire Boards and Cathode Ray Tubes by Municipal Solid Waste Landfill Leachates

Abstract: The proper management of discarded electronic devices (E-waste) is an important issue for solid waste professionals because of the magnitude of the waste stream and because these devices often contain a variety of toxic metals (e.g., lead). While recycling of E-waste is developing, much of this waste stream is disposed in landfills. Leaching tests are frequently used to characterize the potential of a solid waste to leach when disposed in a landfill. In the United States, the Toxicity Characteristic Leaching P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 15 publications
(23 reference statements)
4
111
4
Order By: Relevance
“…Previous e-waste studies (e.g., [13][14][15][16] have shown that Pb exceeds the regulatory standards according to TCLP, although at a much lower concentration than the average 87.42 mg L -1 reported in the present study. This discrepancy is likely due to two factors.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Previous e-waste studies (e.g., [13][14][15][16] have shown that Pb exceeds the regulatory standards according to TCLP, although at a much lower concentration than the average 87.42 mg L -1 reported in the present study. This discrepancy is likely due to two factors.…”
Section: Resultscontrasting
confidence: 62%
“…Several studies have used various leaching procedures to characterize e-waste (13)(14)(15)(16), and they demonstrate that Pb is the metal that most frequently exceeds regulatory thresholds for hazardous waste at all jurisdictional levels. Therefore, regulatory agencies have focused on replacing Pb in electronic products (2).…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded that lead concentration is inversely proportional to its lead recovery rate. Third, the concentrations that exceed the regulatory limit of 5.0 mg/L for TCLP lead [25,26] all have a lead recovery rate lower than 96%, as seen in Table 3. Thus, for safe treatment of funnel glass, it is necessary to obtain a relative higher lead recovery rate, such as higher than 96%, to meet the TCLP lead threshold.…”
Section: Properties Of the Foam Residuesmentioning
confidence: 99%
“…Hundreds of small and open specialized E-waste recycling shelters or yards appear in this area. Many toxic ingredients such as lead, cadmium, beryllium, mercury, polychlorinated biphenyls and brominated flame retardants contained in these Ewastes, (Schmidt, 2002;Soderstrom and Marklund, 2002;Jang and Townsend, 2003;Wong et al, 2007) may enter into the environment and impose great threat to human health regardless of occupational and environmental exposure. The unregulated processing of E-waste usually recovers gold and other valuable metals by applying some simple techniques such as burning, melting, using acid chemical bath, and so on.…”
Section: Introductionmentioning
confidence: 99%